Cobalamin and folate status in women during early pregnancy in Bhaktapur, Nepal. (9th August 2021) - Schwinger, Catherine; Sharma, Shakun; Chandyo, Ram K.; Hysing, Mari; Kvestad, Ingrid; Ulak, Manjeswori; Ranjitkar, Suman; Shrestha, Merina; Shrestha, Laxman P.; McCann, Adrian; Ueland, Per M.; Strand, Tor A.
Abstract: The demand for cobalamin (vitamin B12) and folate is increased during pregnancy, and deficiency during pregnancy may lead to complications and adverse outcomes. Yet, the status of these micronutrients is unknown in many populations. We assessed the concentration of cobalamin, folate and their functional biomarkers, total homocysteine (tHcy) and methylmalonic acid (MMA), in 561 pregnant women enrolled in a community-based randomised controlled trial in Bhaktapur, Nepal. Plasma concentrations of cobalamin, folate, tHcy and MMA were measured and a combined indicator of vitamin B12 status (3cB12) was calculated. We report mean or median concentrations and the prevalence of deficiency according to commonly used cut-offs, and assessed their association with indicators of socio-economic status, and maternal and dietary characteristics by linear regression. Among the women at gestational week less than 15, deficiencies of cobalamin and folate were seen in 24 and 1 %, respectively. Being a vegetarian was associated with lower plasma cobalamin, and a higher socio-economic status was associated with a better micronutrient status. We conclude that cobalamin deficiency defined by commonly used cut-offs was common in Nepalese women in early pregnancy. In contrast, folate deficiency was rare. As there is no consensus on cut-off points for vitamin B12 deficiency during pregnancy, future studies are needed to assess the potential functional consequences of these low values.